PUTUSAN PEMIDANAAN TERHADAP ANGGOTA MILITER YANG MELAKUKAN TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENYEBABKAN ORANG LAIN MENINGGAL DUNIA - Ndruru, Damai Selamat (Jurnal Panah Hukum, 2025)
An event that results in damage when a motor vehicle collides with another item is called a traffic accident. These mishaps can occasionally cause harm or even death to people or animals. A panel of judges at the Military Court I-05 Pontianak is trying one of the criminal actions related to a traffic accident that results in the death of another person; this case is represented by Decision Number 23-K/PM I-05/AD/IV/2017. In this ruling, the judge found that the defendant had been legally and persuasively shown guilty of operating a motor vehicle negligently, which caused a collision that claimed another person's life. The defendant was given a seven-month jail sentence. The study judgment number 23-K/PM I-05/AD/IV/2017 is titled "Criminal decisions for military members who commit criminal acts in traffic accidents that cause other people to die." Normative legal research employing the statutory approach, case approach, and analytical method is the sort of study that is done. Primary, secondary, and tertiary data were used in the data gathering process. Deductive reasoning is employed to arrive at conclusions from the descriptive qualitative data analysis. The military member should not have been penalized despite the fact that his conduct met the requirements of a criminal crime under Article 310 paragraph (4) of Law Number 22 of 2009 concerning Road Traffic and Transportation, according to the study findings and debate. Since the issue has been settled peacefully or restoratively, as indicated by the chronology of the case and witness testimony, the issue that is presently before trial must be dismissed.